1994
DOI: 10.1002/jcp.1041600324
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of phenol sulfotransferase expression in cultured bovine bronchial epithelial cells by hydrocortisone

Abstract: One conjugative pathway for the inactivation of endogenous and exogenous hydroxylated aromatic compounds is catalyzed by phenol (aryl) sulfotransferases (PSTs), which esterify phenolic acceptors with sulfate. The tracheobronchial epithelium is commonly exposed to phenolic drugs and pollutants, and metabolic sulfation and PST activity in this tissue have been previously demonstrated. To determine what factors may control PST expression, extracts of serum-free, growth factor-supplemented cultures of bovine bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
5
17
0
Order By: Relevance
“…The first such demonstrations were performed in cultured bovine adrenocortical cells, where it was shown that glucocorticoid treatment produced substantial increases in SULT1A1 enzyme activity and mRNA content [21,22]. Subsequent studies in vivo and in primary cultured rat hepatocytes indicated that glucocorticoids regulate the expression of rat hepatic SULT1A1 [23].…”
Section: Sult Regulation By Steroid Hormone Receptorsmentioning
confidence: 99%
“…The first such demonstrations were performed in cultured bovine adrenocortical cells, where it was shown that glucocorticoid treatment produced substantial increases in SULT1A1 enzyme activity and mRNA content [21,22]. Subsequent studies in vivo and in primary cultured rat hepatocytes indicated that glucocorticoids regulate the expression of rat hepatic SULT1A1 [23].…”
Section: Sult Regulation By Steroid Hormone Receptorsmentioning
confidence: 99%
“…This tissue has a low basal level of phenol sulfotransferase expression as demonstrated both enzymologically and immunohistologically (Beckmann et al, 1993). Hydrocortisone and other corticosteroids, however, can stimulate the expression of this enzyme in cultured bovine bronchial epithelial cells by 3-5-fold (Beckmann et al, 1994). Here we report that the stimulatory effects of hydrocortisone can be attenuated with retinoic acid, which may have important implications for the dietary control of xenobiotic metabolism in the lung.…”
mentioning
confidence: 62%
“…Cell extracts were prepared by NP-40 detergent lysis method number two as previously described (Beckmann et al, 1994). TotaI protein concentrations were determined by a Coomassie Blue G-250 binding assay (Bio-Rad, Richmond, CA) using bovine serum albumin as the standard.…”
Section: Enzyme Extraction and Analysesmentioning
confidence: 99%
“…SULT1A1 expression was previously observed to be induced by glucocorticoids in cultured bovine tracheobronchial epithelial cells (Beckmann et al, 1994;Schauss et al, 1995). These foundation studies implied a role for steroid receptors in the trans-species regulation of SULT1A1 transcription.…”
Section: Fang Et Almentioning
confidence: 78%